Case series of four psychiatric patients with copy number variations in the neurexin 1 gene. Issue 3 (2nd September 2022) - Kushima, Itaru; Inada, Toshiya; Ohi, Kazutaka; Egawa, Jun; Ozaki, Norio
Abstract :